2015
DOI: 10.1039/c4tc02850c
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of luminescent silver nanoparticles and fluorescence interactions with blue-emitting polyarylene ether nitrile

Abstract: In this work, fluorescent silver nanoparticles with average size of 6 nm were synthesized in an organic phase via a facile one-step reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 71 publications
(34 citation statements)
references
References 40 publications
3
28
1
2
Order By: Relevance
“…42 On the contrary, the co-reduction of metal ions precursor in one-pot reaction was considered as a promising protocol to prepare anisotropic bimetallic gold/silver nanoparticles in a much easier way. In our previous work, 43 the highly luminescent silver nanoparticles with average size of 6 nm were synthesized in the common polar solvent of DMF in the presence of water soluble polymer of PVP, which demonstrated that the silver ions can be readily reduced by DMF to nanoparticles that were stabilized with PVP. Herein, we found that the morphology of prepared nanostructures can be dramatically shaped when small amount of HAuCl 4 precursor solution was introduced into the AgNO 3 /PVP/DMF reaction system under the same experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…42 On the contrary, the co-reduction of metal ions precursor in one-pot reaction was considered as a promising protocol to prepare anisotropic bimetallic gold/silver nanoparticles in a much easier way. In our previous work, 43 the highly luminescent silver nanoparticles with average size of 6 nm were synthesized in the common polar solvent of DMF in the presence of water soluble polymer of PVP, which demonstrated that the silver ions can be readily reduced by DMF to nanoparticles that were stabilized with PVP. Herein, we found that the morphology of prepared nanostructures can be dramatically shaped when small amount of HAuCl 4 precursor solution was introduced into the AgNO 3 /PVP/DMF reaction system under the same experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Для формирования покрытий, содержащих эти наночастицы, был использован полимерно-солевой метод, подробно описанный в [7,8,11]. Образование наночастиц серебра в растворе происходило в результате восстановления ионов Ag + поливинилпирролидоном (ПВП) [24][25][26]. Химические составы пленкообразующих растворов представлены в таблице.…”
Section: материалы и методыunclassified
“…Полоса поглощения с максимумом при 305 nm обусловлена наличием в растворе нитратов серебра и других металлов [28,29]. Более длинноволновая полоса поглощения с максимумом ∼ 425 nm определяется плазмонным поверхностным резонансом [25,26,[30][31][32][33][34][35] наночастиц Ag, формирующихся в растворе. Образование наночастиц Ag происходит при восстановлении ионов серебра поливинилпирролидоном [24,26].…”
Section: результаты и обсужденияunclassified
“…The nitrile groups, with strong polar on the aromatic ring, can promote the adhesion of the polymer main‐chain to many substrates and improve the dielectric constant effectively . The aryl ether bonds on the macromolecular main‐chain of PEN facilitate the solubility of PEN in polar organic solvents , such as N , N ‐dimethylformamide (DMF) , tetrahydrofuran , and N ‐methyl‐2‐pyrrolidinone (NMP) , as well as wide range of processing window, making it easily to be processed into different kinds of products . In addition, PEN with different structures have been prepared by changing the monomer, especially the diphenols.…”
Section: Introductionmentioning
confidence: 99%